Entrepreneurial Orientation, Market Orientation on Silversmiths Innovation - Ni Wayan Astiti Pratiwi; I Gede Riana (Penerbit Kemala Indonesia, 2021)
The purpose of this study was to analyze the effect of entrepreneurial orientation and market orientation on innovation. This study was conducted on silver craftsmen in Gianyar, Bali. Here, the population of silversmiths lives at Celuk Village, Gianyar, Bali. In addition, the number of correspondent samples around 89 industries with using purposive sampling technique. The data were collected through distributing questionnaires which were given directly to the silversmith owners. The data has also gone through instrument testing which states that it is valid and reliable. Here, the collected data were analyzed using multiple linear regression analysis techniques to obtain correlation between entrepreneurial orientation and market orientation on innovation. The results show that entrepreneurial orientation and market orientation have a positive and significant effect on innovation with 0,859 R2 value. This research implies that increasing innovation can be done by implementing strategies such as expanding the market through advertising, distribution channels, and implementing marketing strategies. Another implication of this study indicates that the entrepreneurial orientation and market orientation is a culture of the business that must be applied to the artisans because it can accelerate process of creation of organizational innovation.